Hydraulic Conductivity Functions in Relation to Some Chemical Properties in a Cultivated Oxisols of a Humid Region, Delta State, Nigeria - C. N, Egbuchua (Asian Journal of Agriculture and Rural Development, 2014)
The study was conducted to evaluate hydraulic conductivity functions in relation to some soil chemical properties in an oxisols of the tropics. Field and laboratory studies were carried out and data collected, subjected to statistical analytical procedure for computing coefficient of variability and correlation among soil properties. Results of the study showed that hydraulic conductivity functions varied spatially and temporarily across the experimental points with a moderate mean value of 0.0026 cm/h and a coefficient o variation of 31.45% soil chemical properties showed that the soils were acidic with a mean pH value of 5.12. Organic carbon, total nitrogen and available phosphorus were low with mean values of 1.29%, 0.68% and 4.43 mgkg-1. Coefficient of variability among soil properties indicated less to moderately variable. Soil pH had negative correlation with all the soil properties evaluated.